Pengembangan E-LKPD Flipbook Berbasis Virtual Laboratory PhET Guna Meningkatkan Minat Belajar Fisika - Kartika Hajati; Nursakinah Annisa Lutfin; Fadila Rahmadi (JIPFRI (Jurnal Inovasi Pendidikan Fisika dan Riset Ilmiah), 2025)
This study developed a flipbook-based Electronic Student Worksheet (E-LKPD) integrated with the PhET (Physics Education Technology) virtual laboratory as a physics learning material to improve students’ interest in learning physics. The research used a Research and Development (R&D) method with the 4D model: Define, Design, Development, and Dissemination. The participants were Grade X MIPA students of SMAN 3 Majene, physics teachers, and expert validators. The E-LKPD was validated by experts with an average score of 86.59%, categorized as valid. Practicality tests showed very practical results, with 86.93% from student responses and 93.33% from teacher responses. The effectiveness test showed a gain of 60%, which means the E-LKPD is fairly effective in increasing students’ interest in learning physics. These results confirm that the developed PhET-based flipbook E-LKPD meets the criteria of validity, practicality, and effectiveness.